THE EFFECT OF THE LACTATION SEASON ON SOME BIOCHEMICAL BLOOD PARAMETERS OF HOLSTEIN FRIESIAN COWS - Marwa Hussein Razaq Al-Mousawi, Walid Yousef Qassim and Mohammed Abdul-Wahab Ati (Chelonian Research Foundation, 2023)
The experiment was conducted at Taj Al-Nahrain Research Station, north of Diwaniyah Governorate, by using 35 Holstein cows for the period between 1/3/2022 and 15/8/2022, to demonstrate the effect of the milking season on some biochemical characteristics of Holstein Friesian cows, these cows were divided into three seasons as follows: the first season (11 cows), the second season (15 cows), and the third season (9 cows) based on the station’s records. The cows were placed in semi-shaded pens with a length of 140 m and a width of 60 m for each pen, these pens were provided with freely filled water basins, after that, the physiological traits were analyzed in the Physiology Laboratory of the College of Agriculture, University of Basrah. The results indicated a significant increase in potassium concentration for the first and second seasons compared to the third season, there were no significant differences in glucose, cholesterol, triglycerides, albumin, total protein, phosphorus and calcium. Keywords: lactation season, biochemical blood parameters, Holstein Friesian cows.